Hubungan tingkat pengetahuan dan pola perilaku dengan kejadian malaria di Kabupaten Katingan Provinsi Kalimantan Tengah - Darmiah Darmiah; Baserani Baserani; Abdul Khair; Isnawati Isnawati; Yuniarti Suryatinah (Balai Litbangkes Tanah Bumbu, 2017)
Malaria disease is one of the environmental health problems, Health Office of Katingan District Kasongan District Health Center. Katingan Hilir is a malaria endemic area with an API value in 2010 of 5.6 ‰ and is a red zone in malaria stratafication. Malaria discovery rates from 2008 to 2010 always increase. The high rate of malaria morbidity is due to the lack of knowledge level and community behavior pattern.The aim of this research is to know the correlation between knowledge level and behavioral pattern about malaria with malaria incident in Kasongan sub-district of Katingan Hilir district of Katingan Regency. The type of research is analytic, research design using Fisher exact test. The number of respondents in this study was 58 respondents.Chi-square statistical test results with Continuity Correction obtained p-value 0.002 indicates that there is a relationship between the level of knowledge with the incidence of malaria and the results of statistical tests with Fisher exact test obtained p-value 0.002 that there is a relationship between behavioral patterns with malariaincidence.Efforts that can be done, among others, control the factors causing malaria such as the level of knowledge and behavior patterns as well as increasing the extension of public awareness.